Devastating Complications of Metal Strut Migration Following Pectus Excavatum Repair - Stajevic, Mila; Bijelovic, Milorad; Kosutic, Jovan; Simic, Radoje (European Journal of Pediatric Surgery Reports, 2019)
The modified Ravitch technique with metal struts and the Nuss operation have been the dominant operative techniques for treatment of pectus excavatum in the previous decades. We present devastating postoperative complications of a 16-year-old boy after the modified Ravitch procedure for a severe deformity utilizing two metal bars. Four months following surgery, one strut was removed after the displacement noted on a regular postoperative examination. Ten days after the strut removal, the patient complained of lower limb pain but the sensations were attributed to physical inactivity. Two months later, after pain intensification, the boy was diagnosed with bilateral arterial and venous lower limb thromboses and subsequently, the migration of the remaining metal strut intracardially with the free end in the left ventricular cavity embedded in massive thrombi. An urgent cardiac procedure was performed and the bar removed. Postoperatively, the boy made a full cardiac recovery but with severe neurological complications and subsequent death. Migration of metal struts is a rare complication and, except in our case, had been dealt with successfully. This case should emphasize more attention to the postoperative follow-up management of such patients.
Keywords: pectus excavatum; the Ravitch procedure; strut migration; complications